Naturalist intelligence and personality: An understanding students’ responsible environmental behavior - Nina Wirdianti; Ratna Komala; Mieke Miarsyah (University of Muhammadiyah Malang, 2019)
Notwithstanding that many efforts to overcome environmental problems have been carried out by several parties, yet the issues still occur. Improving students’ responsible environmental behavior (REB) can be an alternative to solve environmental problems. This study aimed to analyze the relation between the both variables (i.e. naturalist intelligence and personality) and students’ REB at SJHS 51 of Bandung. The research was carried out using quantitative descriptive method through a correlational approach. Naturalist intelligence, personality, and REB data were collected using questionnaires. The research data were analyzed using multiple linear regression at α = 0.05. The research results showed that there was a relation between: (1) naturalist intelligence and REB;. (2) personality and REB; and (3) the both predictor variables and REB. Therefore, empowering the both competencies (naturalist intelligence and personality) is the essential step to improve students’ REB.